Analysis of savings asset ownership sand duration of illness on ability to purchase first-level health care facility services in Jambi city - Dwi Noerjoedianto; Andi Subandi (Institute of Computer Science (IOCS), 2023)
Asset ownership and savings are the main factors that must be owned in an effort to access health care facilities, along with the uncertainty of the cost of health services. The purpose of this study was to analyze ownership of savings assets and length of illness on the ability to pay fees to first-level health care facilities in Jambi City. The research method used a cross sectional design, with the instrument using a questionnaire to 100 BPJS Mandiri Non Beneficiaries (PBI) participants with accidental sampling technique. Data analysis was carried out quantitatively, with the results of the statistical test showed that there was a relationship between ownership of savings assets and the ability to buy (p value = 0.003) and there was no relationship between length of illness and the ability to buy (p value = 1,000). The conclusion of this research study is that there is a relationship between ownership of savings assets and there is no relationship between length of illness and the ability to pay for health care costs.